Effect of Time of Year on Surgical Outcomes in Patients Undergoing Minimally Invasive Sacral Colpopexy or Uterosacral Ligament Suspension. Issue 12 (December 2022) - Renkosiak, Kaitlin; Bradley, Megan; Dubinskaya, Alexandra; Shepherd, Jonathan P.
Abstract : (Abstracted from Urogynecology 2022;28:561–566) Research across many fields of medicine suggests the existence of the "July effect, " or increased morbidity and mortality at medical teaching institutions due to the influx of new students and trainees (as much as a 10% increase of fatal medication errors). However, other studies suggest similar mortality rates in both teaching and nonteaching hospitals from the months of May to July, which negates the potential existence of the July effect.